Prevalence of and risk factors for sarcopenia in community‐dwelling people: The Vietnam Osteoporosis Study - Duy K. Hoang; Minh C. Doan; Nhan M. Le; Huy G. Nguyen; Lan T. Ho‐Pham; Tuan V. Nguyen (Wiley, 2024)
Abstract Background Sarcopenia is a geriatric disease characterized by the progressive and generalized loss of skeletal lean mass and strength with age. The prevalence of sarcopenia in the Vietnamese population is unknown. This study sought to estimate the prevalence of and risk factors for sarcopenia among community‐dwelling individuals in Vietnam. Methods This cross‐sectional study is part of the ongoing Vietnam Osteoporosis Study project. The study involved 1308 women and 591 men aged 50 years and older as at 2015 (study entry). Whole‐body dual‐energy X‐ray absorptiometry was used to measure the appendicular skeletal lean mass. Anthropometric and clinical data were collected using a structured questionnaire. Sarcopenia was defined according to the criteria proposed by the Asian Working Group for Sarcopenia in 2019. Logistic regression analysis was used to determine the association between potential risk factors and sarcopenia. Results The prevalence of sarcopenia in women and men was 14% (n = 183) and 16% (n = 83), respectively. Age (odds ratio [OR] per 10 years = 1.37; 95% confidence interval [CI] 1.26-1.48) and being underweight (OR = 1.61; 95% CI 1.00-2.58) were independently associated with increased risk of sarcopenia. The combination of low physical activity, being underweight and advancing age accounted for ~27% of sarcopenic patients. However, most of the attributable fraction was due to ageing. Conclusions Sarcopenia is common in community‐dwelling Vietnamese adults, particularly those with advancing age, who are underweight and with low physical activity.